Improving the clinical management of women with borderline tumours: a recurrence risk scoring system from a French multicentre study. (May 2017) - Ouldamer, L; Bendifallah, S; Nikpayam, M; Body, G; Fritel, X; Uzan, C; Morice, P; Daraï, E; Ballester, M
Abstract : Objective: To develop a risk scoring system (RSS) for predicting recurrence in women with borderline ovarian tumours (BOTs). Design: Cohort study of women with BOTs. Setting: French multicentre tertiary care centres. Population: A cohort of 360 women with BOTs who received primary surgical treatment between January 2000 and December 2013. Methods: Clinical and pathological factors affecting recurrence in women with BOTs. Main outcome measure: The development of a model for the prediction of recurrence in women with BOTs. Results: Overall the recurrence rate was 20.0% (72/360). Recurrence was associated with five variables: age < 45 years; preoperative serum tumour marker CA125 > 150 IU/mL; a serous histological subtype; International Federation of Gynecology and Obstetrics (FIGO) stage other than IA; and ovarian surgery other than bilateral salpingo‐oophorectomy (BSO; i.e. cystectomy and unilateral salpingo‐oophorectomy). These variables were included in the RSS and assigned scores ranging from 0 to 6. The discrimination of the RSS was 0.82 (95% confidence interval, 95% CI 0.79–0.85). A total score of 8 points corresponded to the optimal threshold of the RSS, with a rate of recurrence of 11.8% (35/297) and 58.7% (37/63) for women at low risk (<8 points) and women at high risk (≥8 points), respectively. The diagnostic accuracy was 85.0%. Conclusions: This study shows that the risk of BOT recurrence can be accurately predicted so that women at high risk can benefit from adapted surgical treatment. Tweetable abstract: Our RSS permitted women with BOTs at low risk to be distinguished from women with BOTs at high risk of recurrence. Tweetable abstract: Our RSS permitted women with BOTs at low risk to be distinguished from women with BOTs at high risk of recurrence.